2009
DOI: 10.1521/ijgp.2009.59.3.357
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Behavior Therapy for Early Psychosis: A Comprehensive Review of Individual vs. Group Treatment Studies

Abstract: Several recent studies of individually administered cognitive behavior therapy (CBT) for early psychosis have reported only modest treatment benefits. The purpose of the current study was to review the literature to determine how outcomes of group CBT differ from outcomes of individually administered CBT among early cases. Our findings suggest that group CBT for early psychosis may be a more effective modality for this group of patients. We speculate that patients' uncertainty about illness in general may impa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 82 publications
0
23
0
Order By: Relevance
“…Collaborative team management allowed interventions to be offered in a manner targeting patient and family need but rested finally in patient choice. The FES implementation has been described in published protocols (15),(16) and manuals are available upon request.…”
Section: Methodsmentioning
confidence: 99%
“…Collaborative team management allowed interventions to be offered in a manner targeting patient and family need but rested finally in patient choice. The FES implementation has been described in published protocols (15),(16) and manuals are available upon request.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, depressive symptoms increase the risk of adult asthma independently of health-related lifestyle factors [2]. Group cognitive behavioral therapy (GCBT) is a treatment that reduces therapist hours and treatment costs [3]. Furthermore, GCBT has a consistent positive effect on asthma-related quality of life and depressive symptoms [4].…”
Section: Figmentioning
confidence: 99%
“…The relative benefit of group vs. individual therapy on retention and outcome in BED has received little attention compared to other disorders (Aderka, 2009; Saksa, Cohen, Srihari, & Woods, 2009; Weiss, Jaffee, de Menil, & Cogley, 2004). A single study comparing group and individual cognitive behavioral therapy (CBT) for BED found participants who received individual CBT were more likely to show binge eating remission after 20 weeks (Ricca et al 2010).…”
Section: Treatment Parameters As Predictors Of Treatment Outcomementioning
confidence: 99%